Exploration of lines in landscape painting and architecture / Salmah Ali … [et al.] - Ali, Salmah; Abdul Razak, Haslinda; Dasuki, Shaliza; Khusil@Samuri, Baharim (Faculty of Art and Design, 2024)
Lines are one of the six basic elements in art that are the most dominant and important in the production of works of art. A line is a connection from point A to point B or points connected with a certain distance. Lines also play a very important role in creating looks, shapes, weaves, movements, tones, and patterns. The visual existence of the art of painting is because it is processed using a variety of lines with distinctive line-type characteristics. This study aims to analyze the function of lines that can create the illusion of light and shadow and translate the psychology of lines to human perception. Landscape and architectural images that display the quality of lines are produced through techniques such as "continuous line drawing" and "gesture". The data collected to analyze this study is from a series of paintings that have been produced during trips to holiday locations namely Penang, Melaka, and Pahang. The appreciation method used is based on the formalistic analysis expressed by the 19th-century art critic Roger Fry through observation and comparison to evaluate the function of lines and psychological perception. The findings of this study will help to understand the importance of line elements to create the effect or illusion of reality in the production of 2-dimensional paintings.